Thermochromic Polymer Nanocomposites for the Heat Detection System: Recent Progress on Properties, Applications, and Challenges - Supian A.B.M.; Asyraf M.R.M.; Syamsir A.; Najeeb M.I.; Alhayek A.; Al-Dala?ien R.N.; Manar G.; Atiqah A. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Reversible thermochromic polymers have emerged as compelling candidates in recent years, captivating attention for their application in heat detection systems. This comprehensive review navigates through the multifaceted landscape, intricately exploring both the virtues and hurdles inherent in their integration within these systems. Their innate capacity to change colour in response to temperature fluctuations renders reversible thermochromic nanocomposites promising assets for heat detection technologies. However, despite their inherent potential, certain barriers hinder their widespread adoption. Factors such as a restricted colour spectrum, reliance on external triggers, and cost considerations have restrained their pervasive use. For instance, these polymer-based materials exhibit utility in the domain of building insulation, where their colour-changing ability serves as a beacon, flagging areas of heat loss or inadequate insulation, thus alerting building managers and homeowners to potential energy inefficiencies. Nevertheless, the limited range of discernible colours may impede precise temperature differentiation. Additionally, dependency on external stimuli, such as electricity or UV light, can complicate implementation and inflate costs. Realising the full potential of these polymer-based materials in heat detection systems necessitates addressing these challenges head-on. Continuous research endeavours aimed at augmenting colour diversity and diminishing reliance on external stimuli offer promising avenues to enhance their efficacy. Hence, this review aims to delve into the intricate nuances surrounding reversible thermochromic nanocomposites, highlighting their transformative potential in heat detection and sensing. By exploring their mechanisms, properties, and current applications, this manuscript endeavours to shed light on their significance, providing insights crucial for further research and potential applications. ? 2024 by the authors.